SEMIOTIC ANALYSIS IN TO ALL THE BOYS TRILOGY MOVIE POSTERS - Putri, Annisa Eka; Nurochman, Nurochman (Universitas Gunadarma, 2021)
In movie industry, posters are one of the most powerful media and important to advertise something and deliver some information to the public. Posters contain two elements: verbal (script) and visual (visual art). The problem of this research are: (1) what are semiotic signs that found in To All The Boys trilogy movie posters and (2) how is significance displayed on the verbal and visual signs in To All The Boys trilogy movie posters. The aims of this research are to find out semiotic signs that exists on To All The Boys trilogy movie posters and to describe the significance that displayed on the verbal and visual signs in To All The Boys trilogy movie posters. This research uses qualitative method by using Ferdinand De Saussure signification theory. As a result, the writer found verbal and visual sign in the object of this research. The verbal signs are shown through the ads line, movie title, movie distributor, tagline, release date, and movie logo. Meanwhile, the visual signs are shown through the background illustration of the poster, the character placement in the poster, and colors.